Enhanced TCPW's fast retransmission and fast recovery mechanism over high bit errors networks - Al-Hasanat M.; Seman K.; Saadan K. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by WOS/ Scopus